PENGARUH LEVERAGE DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN INDUSTRI JASA SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2016-2019) - Bagas Wahyu Adi Saputro; Diana Gustinya (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The Effect of Leverage and Managerial Ownership on Earnings Management (Empirical Study on Transportation Sub-Sector Service Industry Companies listed on the Indonesia Stock Exchange for the 20162019 period). This study aims to analyze the effect of leverage and managerial ownership on earnings management in the transportation sub-sector suit industry companies listed on the Indonesia Stock Exchange for the 2016-2019 period. This study uses a purpose sampling method. The analysis technique in this research is multiple linear regression analysis which is used to test the research hypothesis. The total population in this study were 45 transportation service industry companies listed on the Indonesia Stock Exchange for the 20162019 period. There are 15 companies that meet the sample criteria for 4 consecutive years. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX). Based on the results of this study, it states that, partially (t test) the leverage variable has a significant effect on earnings management, managerial ownership variable does not have a significant effect on earnings management. Simultaneously (F test) the leverage and managerial ownership variables have a significant effect on earnings management.